In defense of dualism: Competing and complementary frameworks in religious studies and the sociology of religion - Wood, Richard L. (Critical research on religion, 2016)
The term "dualism" is used in quite divergent connotations across religious studies, sociology, theology, anthropology, and other academic fields. This paper characterizes the differing usages of the term, and uses them to explore the sometimes-converging and sometimes-orthogonal relationship between academic fields, with a focus on religious studies and the sociology of religion. I argue that although the two fields have mutually benefited from insights originating on either side of their divide-and thus converged in important ways-substantive differences remain. Their differing understandings of "dualism" represents important theoretical and analytic divergence, and the justified critique of certain forms of dualism has been used to reject all versions of the concept, including some-here termed "embodied dualism" or "experiential dualism"-that remain analytically crucial to the study of social life generally and religion particularly.